Population Growth and Economic Development in the Philippines: What Has Been the Experience and What Must Be Done? - Aniceto Jr. C. Orbeta; Ernesto M. Pernia (Philippine Institute for Development Studies (PIDS), 1999)
The paper reviews the continuing debate on the interrelationships between population growth and economic development with particular attention to its relevance to Philippine socioeconomic development. The aim is to put the development history of the country in perspective so that a stronger resolve to address the population problem is established. The paper also discusses the prospects for the economy given the high population growth rate and the options for the Philippine population program.
Keywords: 330; demographic economics; public policy